Negro e ensino médio: representações de professores acerca de relações raciais no currículo - SILVA, Rosângela Maria de Nazaré Barbosa e (2009)
This study one consisted is an analysis of the teachers representations about the racial relations in the scholar curriculum of the High School. The analysis is produced from the concept of Representations in the perspective of Roger Chartier (1990;1991) and the contemporary studies about the racial relations and education. Associated to this concept, we used as the methodological way the Analyses of Speech (BARDIN, 1977; ORLANDI, 2004), in two steps. First the analysis of official and scholar documents were made with the objective of understand the materialization of the speech which the symbolical forms were produced and reproduced by the High School which tried to integrate the technical analysis of the Speech. The second step refers to the analysis of the oral documents, constituted of teachers speech from the High School. The results of the oral documental analysis give us two dimensions: the first corresponds to the education process anti-racist, which depends on the subversion of the teachers in the moving one to the contaminated representations of preconceptions, explicit or not, present in their pedagogical practices what will influence the students performance. The second dimension correspond to the need of the naturalization (or de-naturalization) pedagogically speaking. Anyway, such change only will be possible when the teacher develop knowledge to confront the question in the classroom by the curriculum, recognizing its theoretical and procedural singularity. Among this, we conclude that the teachers of History, Arts and Literature still are not integrating their pedagogical actions according to the Brazilian law Lei n 10.639/03.